Assessing the impacts of climate change and other factors on the yield of cavendish banana in Tagum City - Pepio, Hillary Angelica C.; Gomez, Aurelia Luzviminda V. (2018)
Climate change can be revealed by the changes in extremes of temperature and precipitation. The agriculture sector is considered as the most vulnerable to climate change because of its dependence on climate and weather. Climate change, with other factors like farmer?s socio-demographic variables, product inputs, and adaptation practices affect the production of export crops including the Cavendish banana. This study aims to assess how these factors affect the Cavendish banana yield in Tagum City, Davao del Norte. A key informant interview was conducted prior to the actual data gathering to obtain the recent adaptation practices done by the farmers. A total of 104 Cavendish banana farmers were interviewed using a survey questionnaire. Tobit Regression was used to analyze the data gathered from farmers. Results show that these factors had varying effect on Cavendish banana yield in Tagum City. Climate change awareness and farmer?s access to climate information had statistically significant negative effect on yield. Actual climate data show statistically significant differences in annual average temperatures and annual average rainfall experienced in Tagum City from 2008 to 2017. Even with significant variation in climatic data, there was no significant difference in Cavendish banana yield. Factors that were found to have statistically positive impact on yield were farmer?s income, labor, fertilizer and some adaptation practices (replanting a modern variety, using drip irrigation, and avoiding the use of contaminated water). Factors that had significantly negative effect on yield were education, farm size and using drainage canal. Applying appropriate and necessary adaptation practices, depending on farm land and location, is one of the primary recommendations of the study.
Thesis (BS Agribusiness Economics) -- University of the Philippines Mindanao, May 2018